The Phenomenon of Migration and Demographic Change: Its Threats to Identity in the Kurdistan Region After the Year 2014 - Analytical Study: - Hamza, لاجان; Ahmad Amin, کامران (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
The Kurdistan Region has been undergoing a prolonged period of social, conomic, and political instability over the past decade. Consequently, migration, particularly among youth, has emerged as a prominent and significant phenomenon. A large proportion of the youth in the Kurdistan Region exhibit pessimism regarding the current situation, leading many to experience a sense of hopelessness about their future. The migration of youth carries a variety of social, economic, and political consequences, both positive and negative, for the individuals involved, their families, and the broader society of the Kurdistan Region.The aim of this study is to examine the challenges that have affected social security in the Kurdistan Region and to assess their impact on demographic changes, including migration.